Analysis of the factors determining social media instragram as promotion media on the online shop in DKI Jakarta area - Restu Hazar; Resista Vikaliana (STIE Binaniaga, 2020)
Social media is basically regarded as one kind of communication media. Social media in general is a medium used to socialize (connection, either personal or group and so on) among the users, it is not any exception, Indonesia's business community is Instagram social media. Instagram is one of the social networking apps used to share photos and videos that allow users to take photos and share them with followers. This way is used by online shop to promote its products. This study aims to determine and analyze the factors that determine Instagram social media as a campaign media on the online shop 1) Cognitive, 2) Affective, 3) Personal Integration, 4)Social Integration, 5) Release Tension, 6) Accessibility, 7) Relative Cost, 8) Life Style Envy about 3 online shops @elzattahijab, @zoyalovers, and @rabbaniprofesorkerudung_shop which are selling or offering women's clothing. This research uses descriptive qualitative method. Informant in this research is divided into 2 (two) that is key informant and main informant. Data analysis using comparative constant model The process of data analysis includes data reduction, data category,and sisntesisation. The 8 (eight) factors that determine social media Instagram as media promotion on the online shop and there are 7 (seven) factors that determine the online shop @elzattahijab, @zoyalovers, and @rabbaniprofesorkerudung using Instagram as a media campaign on their online shop which is, cognitive, affective , personal identity, social identity, release of tension, easy accessibility, relative reasonable cost factors. For life style envy or jealousy lifestyle, online shop does not feel this factor has become one of the use of social media Instagram as a media campaign on their online shop. And researchers have found one factor that become online factor shop @elzattahijab, @zoyalovers, and @rabbaniprofesor kerudung using Instagram as a media campaign, the innovation feature on Instagram is Insta Stories and live broadcast. Keywords: Promotion, Instagram, Online Shop